Implementation of Land Auctions as Guarantee for Debt Repayment - Bagus Pamungkas, Dewantara; Andria Luhur Prakoso (Journal of Judicial Review, 2024)
Execution is the creditor's ultimate step. If the debtor fails to comply with the conditions of Law No.4 of 1996 respecting Mortgage Rights over Land and Related Objects, an auction or execution may be held. The fundamental challenge in this study is how to conduct an auction of mortgage rights on property as collateral for debt repayment. What are the hurdles to auctioning mortgage rights on land as collateral for debt repayment? This research is classed under Survey or Empirical Law. Meanwhile, the character of this study is descriptive. The research focuses on auction implementation at Bank BPR Wonogiri and BKK Wonogiri. The results of this research is that the auction process carried out by Bank BPR Wonogiri, if the debtor is in default, is carried out at a public auction through the State Property and Auction Service Office or by selling privately. Auctioning mortgage rights is a bit hampered because in the current situation it is difficult to find buyers and auctions are lacking. The findings of this study indicate that if a debtor is in default, Bank BPR Wonogiri conducts a public auction through the State Property and Auction Service Office or sells privately. Auctioning mortgage rights is complicated by the existing difficulty in finding purchasers and the scarcity of auctions.  The obstacles faced were that when executing the promise, it did not work effectively, there was a third lawsuit, the binding of the mortgage was not carried out perfectly, interference from third parties during the execution and disagreements regarding the auction price between the debtor and the auction official.